Effect of digital game addiction on happiness and meaning of life in adolescents - Kaya, Ayla (Journal of Dependence, 2021)
Objective: This study was carried out to determine the effect of digital game addiction on happiness and the meaning of life in adolescents. Method: This study, which is a correlational type, was conducted between January and March 2021. The sample of the study consisted of 162 adolescents between the ages of 13-18 who were studying in two high schools in Antalya. In the application and evaluation of the research data, "Perso Questionnaire" and " Meaning in Life Questionnaire High School Form" were used. The data were obtained through an online questionnaire. Results: Adolescents were in the risk group in terms of digital game addiction, and their happiness and meaning of life were moderate. It was determined that there is a negative and moderate relationship between digital game addiction and happiness in adolescents, and a negative and low level of relationship between digital game addiction and the meaning of life. Digital game addiction has an impact on happiness and the meaning of life. Conclusion: As digital game addiction decreases in adolescents, the level of happiness and meaning of life increases. In addition, as the level of happiness increases, the level of meaning of life increases in adolescents.